1997
DOI: 10.1007/s004310050563
|View full text |Cite
|
Sign up to set email alerts
|

The influence of growth hormone monotherapy and growth hormone in combination with oxandrolone or testosterone on thyroxid hormone parameters and thyrxine binding globulin in patients with Ullrich- Turner syndrome

Abstract: The observed changes in thyroid hormone and TBG levels in the Ox group were not mediated by GH or IGF-I. The Ox-induced TBG decrease might be linked to altered pancreatic functions regulating carbohydrate metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…Administration of GH has yielded conflicting results concerning its role on thyroid function in TS girls as well as in patients with other growth diseases. 12,[24][25][26] The significant increase in TT 3 serum levels recorded in this study is in consonance with reports indicating an increased conversion of T 4 to T 3 induced by GH 27 and with our previous results indicating that IGF-I administration increased TT 3 serum levels in the rat. 15 Furthermore the elevated TT3 levels may also indicate a state of relative T 3 resistance, as expected from our finding of reduced expression of TRα 1 and β 1 .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Administration of GH has yielded conflicting results concerning its role on thyroid function in TS girls as well as in patients with other growth diseases. 12,[24][25][26] The significant increase in TT 3 serum levels recorded in this study is in consonance with reports indicating an increased conversion of T 4 to T 3 induced by GH 27 and with our previous results indicating that IGF-I administration increased TT 3 serum levels in the rat. 15 Furthermore the elevated TT3 levels may also indicate a state of relative T 3 resistance, as expected from our finding of reduced expression of TRα 1 and β 1 .…”
Section: Discussionsupporting
confidence: 93%
“…In TS patients, the effect of GH treatment was reported by Massa et al 24 . and Schmitt et al 25 . who did not find significant changes in TSH serum level after GH administration.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…1,2001 chromosome has been shown to be involved in short stature associated with Turner's syndrome". 1,2001 chromosome has been shown to be involved in short stature associated with Turner's syndrome".…”
Section: Discussionmentioning
confidence: 99%
“…No changes in thyroid parameters were found in a placebo-controlled, double-blind trial of GH therapy (0AE222 mg/kg/week) in non-GHD short children. 22 Of four studies identified using variable pharmacological doses of GH therapy in girls with Turner's syndrome, two demonstrated no change in thyroid parameters 62,63 one showed a decrease in free T4 within the normal range at 6 months of therapy that returned to baseline at 1 year without any alteration in T3 64 and the most recent study found a trend towards a decrease in free T4 and an increase in T3 and TSH, all within the normal range. 65 None of the subjects became clinically or biochemically hypothyroid during GH administration, suggesting that GH unmasks rather than induces CH in at risk groups with organic pituitary disease.…”
Section: Growth Hormone Effect On the Thyroid Axismentioning
confidence: 99%